#TITLE_ALTERNATIVE# - TAMBUNAN (NIM : 22106338), CHARLES
Technology exploration of natural resources continue to be developed along with the increasing human need for natural resources. Geophysical method is a powerful enough method to map the natural resources beneath the earth's surface. Several geop hysical methods that have been widely used for exploration of natural resources such as seismic, gravity, geolistrik, magnetic and Very Low Frequency (Very Low Frequency / VLF). One method that can detect both metallic minerals are methods of Very Low Fre quency Electromagnetic (Very Low Frequency / VLF). This method is a passive method, for measuring the magnitude of this anomaly is the amount of rock conductivity in the earth. Research conducted in Tanggamus District, Lampung Province. Geographically, the location is located in the interval coordinates: 1040 41' -1040 44' BT dan 050 28' - 070 33' LS. From the results of field measurements obtained price in -phase anomaly ranges from -74% to 234% while the price of Quadrature anomaly between -2% to 25%. This was formed because of the research area of rock un - uniformity. 2D modeling shows that the expected depth of the conductive objects range from 0 - 200 m, even the depths of the northern area suspected to 300 m. Conductive objects are interpreted as a result of the breakthrough rock (intrusion) which consists of granite and granodiorit.